PENGARUH AUTHENTIC LEADERSHIP TERHADAP MENTALITAS SIAP BERUBAH DAN KINERJA PEGAWAI PARUH WAKTU - Masduki Asbari; Dewiana Novitasari (Universitas Bunda Mulia, 2021)
This study aimed to measure the effect of authentic leadership on employee performance of the part-time employee of a manufacturing company in Tangerang which is mediated by readiness for change mentality. Data collection was done by simple random sampling technique and the returned and valid questionnaire results were 109 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that authentic leadership has a significant effect on readiness for change and employee performance. This study conclude also that readiness for change have a positive and significant effect on the relationship between authentic leadership and employee performance. Readiness for change as a mediator. This new research proposed a model for building employee performance among the part-time employee of the manufacturing industry in Tangerang through enhancing authentic leadership practice with readiness for change as a mediator. This research could pave the way to improve employee readiness in facing the era of industrial revolution 4.0.